Dampak Tata Pemerintahan yang Baik terhadap Kepercayaan Masyarakat Kabupaten Pasaman - Nurhatika Nurhatika; Deviani Deviani (Jurnal Eksplorasi Akuntansi, 2023)
This research aims to find out how much impact good governance has on the trust of the people of Pasaman district. This research uses legitimacy theory. The population of this study was the people of Pasaman district and data collection was carried out using a questionnaire which was distributed directly to 400 people of Pasaman district who were at least 17 years old, had a minimum of high school education, and people who had had dealings with the government. The research results show that 77.4% of good governance variables can influence public trust variables while the rest are influenced by other variables.